CORRELAÇÃO DA DISFUNÇÃO DO VENTRÍCULO DIREITO AVALIADA PELO TAPSE COM A CLASSE FUNCIONAL E PARÂMETROS CLÍNICOS DE CONGESTÃO EM PACIENTES PORTADORES DE ICFER DO AMBULATÓRIO DE CARDIOLOGIA DO HUMAP-UFMS - Thais Keiko Siroma (2023)
Heart failure with reduced ejection fraction (HFrEF) and right ventricular (RV) dysfunction represent clinical conditions of great impact on public health in the country, since when associated biventricular dysfunction can negatively influence the prognosis of this clinical condition. A analyrical, cross-sectional and quantitative research was carried out in which the echocardiographic parameters of RV function were evaluated by the TAPSE method, the symptoms and clinical outcomes of hospitalizations and deaths in patients with HFrEF and right ventricular dysfunction, aiming at an in-depth understanding of the clinical profile of this population. The methodology comprised the collection of secondary data obtained from the RedCap platform from patients at the heart failure outpatient clinic of the University Hospital Maria Aparecida Pedrossian (HUMAP), in Campo Grande, Mato Grosso do Sul, from July 2021 to December 2022, mapping the clinical characteristics and complementary exams of patients with chronic heart failure. In addition to the secondary data from the platform, the echocardiograms attached to the medical records of these patients were analyzed, with the collection of additional data such as the systolic function of the right ventricle evaluated by the TAPSE method, the systolic pressure of the right ventricle (RVSP) and the dimensions of the right ventricle. We evaluated 108 patients with HFrEF aged 18 years or older and ejection fraction (EF) less than 50%. Of the total number, 46,3% had RV dysfunction, and of these (n=50), 78% (95%CI:36,7% to 56,2%) had RV systolic function assessed using the TAPSE method. Trough the bivariete analysis between the clinical signs of congestion, life habits, comorbidities, LV and RV echocardiographic parameters, and the occurrence of clinical results, it was observed that there is an association of RV dysfunction with the presence of diabetes, in addition to lower values in LVEF. There were no concrete results with clinical outcomes in patients with HfeEF and right ventricular dysfunction, with a low number of deaths. However, the clinical importance of adequate evaluation of the RV in patients with HfrEF and studies focused on the RV for the elaboration of therapies that can improve its function and promote improvements in the prognosis of patients is highlighted.